The Effect of Discovery Learning Through Computer Assisted Instruction in Developing Science Processes of Third Grade Students in Jordan - Al-Abbadi, Hamed; Al-Sheboul, Fathieh (Jordan Journal of Educational Sciences, 2007)
The study aimed at investigating the effect of discovery learning through computer-assisted instruction (CAI) compared with the discovery and traditional methods of learning in developing science processes of observation, categorization, and prediction of third grade Jordanian students. A sample of 90 Jordanian students was purposefully chosen and distributed into three groups. A unit from the third grade science textbook was used to teach the three groups according to the discovery method through CAI, discovery learning, and the traditional method. The results of the study revealed that students taught according to the discovery method through CAI exceeded their counterparts in the other two groups regarding the achievement of the three science processes, and that the achievement of students who were taught by the discovery learning method exceeded that of those taught by the traditional method in the three science processes. Based on these findings, appropriate recommendations were presented.